Efficacy and Safety of Filgotinib in Patients with High Risk of Poor Prognosis Who Showed Inadequate Response to MTX: A Post Hoc Analysis of the FINCH 1 Study - Bernard G. Combe; Yoshiya Tanaka; Maya H. Buch; Peter Nash; Gerd R. Burmester; Alan J. Kivitz; Beatrix Bartok; Alena Pechonkina; Katrina Xia; Kahaku Emoto; Shungo Kano; Thijs K. Hendrikx; et al. (Rheumatology and Therapy, 2022)
Abstract Introduction This exploratory analysis of FINCH 1 (NCT02889796) examined filgotinib (FIL) efficacy and safety in a subgroup of patients with rheumatoid arthritis (RA) and inadequate response to methotrexate (MTX; MTX-IR) who had four poor prognostic factors (PPFs). Methods Patients with MTX-IR received placebo up to week (W)24 or FIL200 mg, FIL100 mg, or adalimumab up to W52; all received MTX. Efficacy and safety data were stratified by four PPFs versus fewer than four PPFs: seropositivity, high-sensitivity C-reactive protein (CRP) ≥ 6 mg/L, Disease Activity Score in 28 joints with CRP > 5.1, and erosions on X-rays. Results At baseline, 687/1755 patients had four PPFs. At W12, whether with four PPFs or fewer than four PPFs, response rates on all American College of Rheumatology (ACR) measures were significantly greater with FIL200 and FIL100 versus placebo. At W52, FIL200 ACR20/50/70 response rates remained at least numerically higher versus adalimumab in both subgroups. At W52, FIL200 reduced modified total Sharp score (mTSS) change versus adalimumab in patients with four or fewer than four PPFs. Conclusions In high-risk (four PPFs) patients with MTX-IR RA, FIL200 and FIL100 showed similar reductions in disease activity versus placebo at W12 as in patients with fewer than four PPFs. mTSS in patients receiving FIL200 changed little from W24 to W52, while that in patients receiving FIL100 progressed comparably to patients who received adalimumab. Tolerability was comparable across treatment arms and subgroups.